We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
380
1
avatar

5(7f-3)=28(f-1)

 Jul 9, 2015

Best Answer 

 #1
avatar+14537 
+5

5*(7f-3) =28*(f-1)

35f -15 = 28f -28                     |  -28f   and  +15

7f = -13      =>    $${\mathtt{f}} = {\mathtt{\,-\,}}{\frac{{\mathtt{13}}}{{\mathtt{7}}}}$$

.
 Jul 9, 2015
 #1
avatar+14537 
+5
Best Answer

5*(7f-3) =28*(f-1)

35f -15 = 28f -28                     |  -28f   and  +15

7f = -13      =>    $${\mathtt{f}} = {\mathtt{\,-\,}}{\frac{{\mathtt{13}}}{{\mathtt{7}}}}$$

radix Jul 9, 2015

9 Online Users

avatar
avatar